Evaluating the Quality of Clothes and Gloves Used in the Hospitals in Saudi Arabia - Sami, Abdelhalim; Al Owad, Ali (Journal of King Abdulaziz University: Engineering Sciences, 2022)
In a hospital, doctors use anesthetic gases during operations. Some of these gases are explosive. If the gas escapes into the air, a tiny spark from static charge could make it explode. The reduction or avoidance of static charge in operating theatres and other rooms is necessary. The present work aims to investigate the quality of textiles in hospitals in terms of the electrostatic charge generated from the contact and separation. This can be achieved by studying the sliding of latex gloves of doctors, nurses, and other workers in hospitals against the textiles of clothes in dry working conditions. Based on the results, the amount of static charge collected on the textile surface determines its quality. The finest grade textiles have the lowest static charge values. The static charge is created when sliding the gloves accumulates charge on the material and clothing. In dry conditions, the larger value of static charge was 240 volts, as shown on yellow clothing worn by physicians in operating theatres. For safe working in various workplaces, It's indeed necessary that pay careful attention to the particulars that impact performance in order to enhance the working environment of health care professionals. The following quality management policies and selection of textiles and clothing based on electrostatic charge is strongly advised. Hand and glove performance is extremely important for health care professionals. Glove makers, hospital administration, and health-care personnel all need to be more aware of the issues surrounding gloves. There is a need for procedures and tools that can detect issues with medical gloves.